2015
DOI: 10.1007/s10750-015-2205-5
|View full text |Cite
|
Sign up to set email alerts
|

Health and reproduction of red mullet, Mullus barbatus, in the western Mediterranean Sea

Abstract: Ferrer-Maza, D.; Muñoz, M.; Lloret, J.; Faliex, E.; Vila, S.; Sasal, P. (2015). Health AbstractThe reproductive and general health of exploited fish stocks is an essential element of sustainable and profitable fisheries. The main purpose of this study is to assess the relationships between reproduction and two important parameters of fish health (parasitism and energy reserves) in female specimens of red mullet, Mullus barbatus, from the western Mediterranean Sea. We present new data for this species on (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The values of fecundity reported in the present study are also coherent with other studies carried out with the European anchovy in the Adriatic Sea ( Casavola et al , 1996 ) or in the northeast Atlantic Ocean ( Sanz and Uriarte, 1989 ; Motos, 1996 ). The batch fecundity was positively related to total length, which means that larger individuals have a higher reproductive capacity than smaller ones, as is commonly the case with several northwestern Mediterranean commercial fish species ( Muñoz et al , 2005 ; Ferrer-Maza et al , 2014 , 2015 ; Villegas-Hernández et al , 2014 , 2015a , b ). In the present study, the size of all the immature anchovy specimens we examined exceeded 9 cm, which is currently the minimal landing size for anchovy in the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The values of fecundity reported in the present study are also coherent with other studies carried out with the European anchovy in the Adriatic Sea ( Casavola et al , 1996 ) or in the northeast Atlantic Ocean ( Sanz and Uriarte, 1989 ; Motos, 1996 ). The batch fecundity was positively related to total length, which means that larger individuals have a higher reproductive capacity than smaller ones, as is commonly the case with several northwestern Mediterranean commercial fish species ( Muñoz et al , 2005 ; Ferrer-Maza et al , 2014 , 2015 ; Villegas-Hernández et al , 2014 , 2015a , b ). In the present study, the size of all the immature anchovy specimens we examined exceeded 9 cm, which is currently the minimal landing size for anchovy in the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 71%
“… Barber and Svensson 2003 ; Bagamian et al , 2004 ; Bean and Bonner 2009 ). However, only a few studies have analysed the relationships between parasitism, energy reserves and reproduction in commercially exploited fish species in the Mediterranean ( Ferrer-Maza et al , 2015 , 2014 ). There is, to our knowledge, only one other study concerning the European anchovy, carried out in the Black Sea, which has looked into the effects of parasites (in this case, nematodes) on the lipid composition of the European anchovy ( Shchepkina, 1985 ).…”
Section: Introductionmentioning
confidence: 99%
“…Along with food availability and reproduction, parasitism has also been identified as a factor affecting the body condition of several fish species in the Mediterranean (e.g. Lloret et al , 2012 ; Ferrer-Maza et al , 2014 , 2015 , 2016 ; Serrat et al , 2019 ). However, to our knowledge, few studies have looked into the effects of parasites on the lipid content of small pelagic fish in the Mediterranean, and those that exist have yielded conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…We made several attempts to collect Lasiotocus mulli (Stossich, 1883) Odhner, 1911 (type-species) but were unsuccessful. Ferrer-Maza et al [60] represents the most recent report of L. mulli collected in the Mediterranean Sea, but personal communication with the primary author revealed that the prevalence of L. mulli was very low in her study. Over 300 specimens of the definitive host were examined, and only 5 specimens of L. mulli were found.…”
Section: Discussionmentioning
confidence: 75%